Extensive profiling of three varieties of Opuntia spp. fruit for innovative food ingredients - Melgar Castañeda, Bruno (2017)
Consumer interest in the use of natural ingredients is creating a growing trend in the food industry, leading to research into the development of natural products such as colorants, antimicrobials and antioxidant compounds. This work involves an extensive morphological (using physico-chemical assays), chemical (antioxidant activity assays) and microbiological (Gram-positive and negative strains) characterization of prickly peras (Opuntia ficus-indica (OFI) var. sanguigna, gialla and Opuntia engelmannii) fruits. Through chromatographic assays, these species have shown interesting contents of hydrophilic (sugars, organic acids and betalains) and lipophilic (tocopherols and fatty acids) compounds. While Opuntia engelmannii exhibited higher content of betacyanins and mucilage, OFI varieties sanguigna and gialla displayed greater organic acid content. The sanguigna variety also showed the highest a-tocopherol content. All this compounds could be the responsible of enhancing the bioactivity of this variety, which can be observed in its antimicrobial potential, tested in the studied strains too. Results revealed that Opuntia spp. could be used as a nutraceutical and/or food additive, maintaining and promoting health and life quality.